2015
DOI: 10.1007/s00382-015-2846-0
|View full text |Cite|
|
Sign up to set email alerts
|

Shallowness of tropical low clouds as a predictor of climate models’ response to warming

Abstract: climatological shallowness of low clouds and thus to the spread of low-cloud changes under global warming.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
165
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(174 citation statements)
references
References 79 publications
8
165
1
Order By: Relevance
“…Recent work has increasingly highlighted the critical role of cloud base cloudiness in determining the climate sensitivity of GCMs (Brient et al, 2015;Vial et al, 2017). The atmospheric stability (EIS or LTS) provides an excellent diagnostic tool with which to determine how parameterized turbulence and convection influence the low-level atmospheric temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has increasingly highlighted the critical role of cloud base cloudiness in determining the climate sensitivity of GCMs (Brient et al, 2015;Vial et al, 2017). The atmospheric stability (EIS or LTS) provides an excellent diagnostic tool with which to determine how parameterized turbulence and convection influence the low-level atmospheric temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed the cloud fraction near the inversion level appears to be more variable than that at cloud base (Nuijens et al 2014), varies strongly with the intensity of the convective mass flux (e.g., Brient et al 2016;Vial et al 2016) and strongly influences the variations of the total cloud cover (Rodts et al 2003). The cloud fraction near the inversion level will be estimated through different methods.…”
Section: Estimating the Distribution Of Clouds In The Trade-wind Bounmentioning
confidence: 99%
“…Their response to global warming is thus critical for global-mean cloud feedbacks, and actually it is their differing response to warming that explains most of the spread of climate sensitivity across climate models (Bony et al 2004;Bony and Dufresne 2005;Webb et al 2006;Medeiros et al 2008;Vial et al 2013;Boucher et al 2013;Medeiros et al 2015). Model diversity in the strength of the vertical mixing of water vapour within the first few kilometres above the ocean surface (in association with both convective and large-scale circulations) is thought to explain half of the variance in climate sensitivity estimates across models (Sherwood et al 2014): the lower-tropospheric mixing dehydrates the cloud layer near its base at an increasing rate as the climate warms and this rate scales with the mixing strength in the current climate (Sherwood et al (2014); Gettelman et al (2012); Tomassini et al (2015); Brient et al (2016); Stevens et al (2016); Vial et al (2016), Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…It has been hypothesized that as SSTs rise, enhanced mixing of the boundary layer air with the drier free troposphere dries out the cloud layer and results in less clouds [e.g., Rieck et al, 2012]. Brient et al [2016] showed that models with a pronounced maximum in low cloud amount at cloud base are most susceptible to convective drying, but not through a reduction of clouds throughout the cloud layer, as shown by Rieck et al [2012], rather by a reduction of cloud amount at cloud base. This effect is pronounced in our simulations, and is robust as it appears irrespective of the domain size.…”
Section: Journal Of Advances In Modeling Earth Systems 101002/2016msmentioning
confidence: 99%
“…However, the total response of low clouds to warming in GCMs results from a balance between drying from the convective parameterization and moistening by the turbulence parameterization. Different balances between these processes were argued [Brient et al, 2016;Sherwood et al, 2014] to be one of the primary factors leading to the spread of total feedback in CMIP models. All of our simulations show (Figure 9) a uniform decrease of cloud liquid water (0.6 km) and a decrease with height of low-level water vapor in response to warming but the response of cloud cover and RH is not systematic across domains.…”
Section: Journal Of Advances In Modeling Earth Systems 101002/2016msmentioning
confidence: 99%